Online application of imagery rescripting for pathological affective dependence (ImRs-PAD) in survivors of intimate partner violence: Results from a multiple case series - Erica Pugliese; Allison Uvelli; Arnold A. P. van Emmerik; Arnoud Arntz (Clinical Psychology in Europe, 2026)
Background This study examined the feasibility and preliminary clinical indications of an imagery rescripting intervention integrating the Pathological Affective Dependence framework (ImRs-PAD) in survivors of Intimate Partner Violence (IPV). Pathological Affective Dependence (PAD) refers to a trauma-related relational vulnerability associated with difficulties in disengaging from abusive intimate relationships. Method A multiple case series design was used with three female IPV survivors referred by a mental health center in Italy (mean age = 31.3 years, SD = 2.08). All participants reported histories of abusive relationships, marked difficulties with separation, and clinically significant levels of PAD. Participants received an online ImRs-PAD intervention. Repeated self-report measures assessed changes in PAD, trauma-related symptoms, depression, anxiety, somatic symptoms, resilience, self-compassion, and psychological well-being. Results Across cases, reductions were observed in PAD, depressive and anxiety symptoms, and trauma-related and somatic complaints, alongside increases in resilience, self-compassion, and overall psychological well-being. The online delivery of the intervention was feasible, with no technical or safety issues reported. Conclusion The findings provide preliminary support for the potential clinical relevance of ImRs-PAD for IPV survivors. Addressing PAD may facilitate disengagement from violent partners and reduce the risk of re-exposure to severe forms of violence.